65.2k views
0 votes
Distribute -4(-x + y)

My answer was -4 * -x + -4 *y
-4x -4y
Did I complete this problem correctly??? If not can you please explain what I did wrong?

2 Answers

7 votes


- 4( - x + y) \\ = (- 4)( - x) + ( - 4)( y) \\ = 4x + ( - 4y) \\ = 4x - 4y
The answer is 4x - 4y
User Bgoncalves
by
6.3k points
4 votes
The answer would be 4x-4y.

(-4 * -x) + (-4 * y)
(4x) + (-4y) = 4x + -4y

Just be careful and remember that a negative times a negative is positive.
User Chuanqi Sun
by
5.4k points